CircCRIM1 Promotes Hepatocellular Carcinoma Proliferation and Angiogenesis by Sponging miR-378a-3p and Regulating SKP2 Expression - Ji, Yang; Yang, Shikun; Yan, Xueqi; Zhu, Li; Yang, Wenjie; Yang, Xinchen; Yu, Fei; Shi, Longqing; Zhu, Xi; Lu, Yunjie; Zhang, Chuanyong; Lu, Hao; et al. (Frontiers in Cell and Developmental Biology, 2021)
Mounting evidence has demonstrated that circular RNAs have an important function in tumorigenesis and cancer evolvement. CircCRIM1 has been shown to be a poor prognostic element in multiple human malignancies. However, the clinical significance and mechanism of circCRIM1 in hepatocellular carcinoma (HCC) is still unclear. The present study confirmed the expression level of circCRIM1 using quantitative real-time PCR. In addition, circCRIM1 siRNA and overexpression vectors were used for transfection into LM3 or Huh7 cells to down- or up-regulate the expression of circCRIM1. In vitro and in vivo experiments were performed to explore the function of circCRIM1 in HCC. RNA pull-down, RNA immunoprecipitation, fluorescent in situ hybridization, and luciferase reporter assays were conducted to confirm the relationship between miR-378a-3p and circCRIM1 or S-phase kinase-associated protein 2 (SKP2) in HCC. Then, circCRIM1 was up-regulated in HCC and its expression level was significantly associated with poor prognosis and clinicopathologic characteristics. CircCRIM1 enhanced the proliferation and angiogenesis of HCC cells in vitro and promoted xenograft growth in vivo. Moreover, circCRIM1 upregulated the expression of SKP2 by functioning as a sponge for miR-378a-3p. These findings suggest that circCRIM1 boosts the HCC progression via the miR-378-3p/SKP2 axis and may act as a crucial epigenetic therapeutic molecule target in HCC.